2020
DOI: 10.1186/s13023-020-01569-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the mutation screening strategy in Marfan syndrome and identifying genotypes with more severe aortic involvement

Abstract: Background Marfan syndrome (MFS) is a systemic connective tissue disorder with life-threatening manifestations affecting the ascending aorta. MFS is caused by dominant negative (DN) and haploinsufficient (HI) mutations of the FBN1 gene. Our aim was to identify mutations of MFS patients with high detection rate and to investigate the use of a gene panel for patients with Marfanoid habitus. We also aimed to examine correlations between genotype and cardiovascular manifestations to predict “malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
(111 reference statements)
0
17
0
Order By: Relevance
“…In case of the latter group, current guidelines could be applied. This approach has been proposed in our previous work for patients with MFS [ 80 ], and the above reviewed results seem to strengthen this potential management strategy.
Fig.
…”
Section: Genotype–phenotype Correlationsmentioning
confidence: 60%
See 1 more Smart Citation
“…In case of the latter group, current guidelines could be applied. This approach has been proposed in our previous work for patients with MFS [ 80 ], and the above reviewed results seem to strengthen this potential management strategy.
Fig.
…”
Section: Genotype–phenotype Correlationsmentioning
confidence: 60%
“…In addition, patients with DN Cys variants required aortic surgery more frequently than patients with HI and DN non-Cys mutations. Therefore, in our study DN Cys mutations appeared to be more deleterious than HI ones [ 80 ]. Similarly, when genotype–phenotype correlations were assessed in a pediatric cohort, missense variants affecting a cysteine showed a higher rate of sinuses of Valsalva dilation than missense mutations not affecting cysteine.…”
Section: Genotype–phenotype Correlationsmentioning
confidence: 94%
“…The second one classified DN variants based on the affected region, including the N-terminus, C-terminus, and neonatal region. Recent studies suggested that DN (-Cys) variants and variants in the neonatal region were closer to HI variants in nature than other DN variants, ( Faivre et al, 2009b ; Stengl et al, 2020 ), while DN (+Cys) variants were associated with fewer aortic events but similarly high incidence of EL when compared to DN (-Cys) ( Faivre et al, 2007 ; Stengl et al, 2020 ; Arnaud et al, 2021a ). A new region was also identified by taking both the protein structure and the variant clusters of extreme phenotypes ( Takeda et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fbn1 -mutant mouse models have been used in numerous studies for several years. The etiology of MFS has been ascribed to dominant-negative effects and haploinsufficiency [ 24 ]. The effect of FBN1 mutations in patients with MFS has been successfully mimicked in mouse models [ 19 ].…”
Section: Marfan Syndrome and Animal Modelsmentioning
confidence: 99%